Cold War experience - Friedman, Norman (Carlton Books, 2009)
Twenty years ago, the Berlin Wall fell and Communism in Europe began to collapse. The Cold War celebrates that anniversary with a graphic account of the long-running global drama that played from the end of World War II until the era of Gorbachev and glasnost. During that time, such high-tension events as the Cuban Missile Crisis brought us to the brink of Armageddon-but both sides always drew back. Follow spread by spread the development of each important stage in the long, chilly conflict that divided the world into two spheres of influence. More than 30 facsimile items of Cold War memorabilia allow readers to hold and examine diaries, letters, telegrams, decoded intercepts, and newspapers that, up till now, were confined to filing cabinets and museum exhibitions.